And the Winner is…︁Azadithiolate: An Amine Proton Relay in the [FeFe] Hydrogenases. Issue 51 (4th November 2013) - Schilter, David; Rauchfuss, Thomas B.
<x xml:space="preserve">Abstract</x> A victory in the pocket: An international team of chemists and biophysicists have resolved the long‐standing question of the structure of the active site of the [FeFe] hydrogenases by assembling the active enzyme with a version of the active site synthesized in vitro (see scheme; HydF is a scaffold protein, HydA1 is a natural hydrogenase). The protein incorporating the diiron complex 2 showed similar activity to that of the natural enzyme.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>